Cardioprotective Actions of TGFβRI Inhibition Through Stimulating Autocrine/Paracrine of Survivin and Inhibiting Wnt in Cardiac Progenitors. (10th October 2015) - Ho, Yu‐Sian; Tsai, Wan‐Hsuan; Lin, Fen‐Chiung; Huang, Wei‐Pang; Lin, Lung‐Chun; Wu, Sean M.; Liu, Yu‐Ru; Chen, Wen‐Pin
Abstract : Heart failure due to myocardial infarction (MI) is a major cause of morbidity and mortality in the world. We found previously that A83‐01, a TGFβRI inhibitor, could facilitate cardiac repair in post‐MI mice and induce the expansion of a Nkx2.5 + cardiomyoblast population. This study aimed to investigate the key autocrine/paracrine factors regulated by A83‐01 in the injured heart and the mechanism of cardioprotection by this molecule. Using a previously described transgenic Nkx2.5 enhancer‐green fluorescent protein (GFP) reporter mice, we isolated cardiac progenitor cells (CPC) including Nkx2.5‐GFP + (Nkx2.5+), sca1+, and Nkx2.5+/sca1 + cells. A83‐01 was found to induce proliferation of these three subpopulations mainly through increasing Birc5 expression in the MEK/ERK‐dependent pathway. Survivin, encoded by Birc5, could also directly proliferate Nkx2.5 + cells and enhance cultured cardiomyocytes viability. A83‐01 could also reverse the downregulation of Birc5 in postinjured mice hearts ( n = 6) to expand CPCs. Moreover, the increased Wnt3a in postinjured hearts could decrease CPCs, which could be reversed by A83‐01 via inhibiting Fzd6 and Wnt1‐induced signaling protein 1 expressions in CPCs. Next, we used inducible α MHC‐cre/mTmG mice to label cardiomyocytes with GFP and nonmyocytes with RFP. We found A83‐01 preserved more GFP + myocytes (68.6% ± 3.1% vs. 80.9% ± 3.0%; p < .05, n = 6) and fewer renewed RFP + myocytes (0.026% ± 0.005% vs. 0.062% ± 0.008%; p < .05, n = 6) in parallel with less cardiac fibrosis in isoprenaline‐injected mice treated with A83‐01. TGFβRI inhibition in an injured adult heart could both stimulate the autocrine/paracrine activity of survivin and inhibit Wnt in CPCs to mediate cardioprotection and improve cardiac function. Stem Cells 2016;34:445–455